Preliminary coronary artery disease (CAD) case and control study of total homocysteine (Hcy), clinico-laboratory and aociodemographic profiling among respondents in Klang Valley, Malaysia - Ahmad, Zalinah; Abang Yusuf, Dayang Sarah Yasmine; Mohamed Yusof, Ahmad Khairuddin; Md Razip, Nurliyana Najwa; Osman, Malina; Ismil, Fatin Izyan (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
Introduction: Coronary artery disease (CAD) is a multifactorial pathogenesis ailment usually associated with hypertension, hyperlipidemia and dysregulated biochemical characteristics. Materials and methods: This case-control study analysed risk factors such as age, gender, ethnicity, BMI, SBP and DBP which have been linked to CAD. TC, TG, HDL, LDL, smoking status, exercise habit, obesity, family history of CVD and tHcy were also assessed to elucidate their association with CAD. Seventy-four respondents were diagnosed as CAD patients with angiography assessment at National Health Institute (NHI) Malaysia. Three hundreds and ten healthy respondents with no CAD signs or history were recruited from NHI, UPM and National Blood Bank (NBB). This study explores sociodemographic and clinico laboratory risk factors which contribute to the CAD conditions. Results: Individuals with CAD had an average age of 53.66 ± 7.904 years old, significantly different with non-CAD respondents average age (32.07 ± 10.080), p<0.05. Malays were found to be the highest prevalent ethnic of having CAD, followed by Indians and Chinese,with p-value <0.05. Respondents with CAD had significantly greater BMI (29.11 ± 3.660) kg/m2 and higher SBP (135.16 ± 7.406) mmHg with p<0.05 compared to non-CAD. Laboratory results for respondents with CAD displayed higher TC (5.025 ± 1.009) mmol/L, TG (1.696 ± 0.222) mmol/L, LDL ( 3.483 ± 0.350) mmol/L and total Hcy levels (9.807 ± 2.149) μmol/L with p-value<0.05. Conclusion: Current preliminary findings ascertained that respondents with CAD were associated withthe risk of age , ethnicity and biochemical characteristics that could be further investigated for future study.